Modified multilevel inverter based an active power filter using fuzzy controller for power quality enhancement - R. Chavan, Pranita; Rajaram Patil, Babasaheb (Bulletin of Electrical Engineering and Informatics, 2025)
Power electronics-based nonlinear loads generate significant current harmonics, adversely affecting the efficiency and reliability of distribution networks. Active power filters (APFs), leveraging power electronics technology, provide an alternative to passive filters in mitigating harmonics. Multilevel inverter-based (MLI) APFs, particularly for high-power applications, offer numerous advantages but often suffer from increased component count and control complexity. In this article, a novel five-level MLI topology is proposed, featuring a reduced number of switches compared to the traditional cascaded H-bridge topology with eight switches. This research reduces system cost and simplifies controller design. To further enhance system performance, a fuzzy logic controller (FLC) is implemented for DC-link voltage control. Harmonics are identified using the instantaneous p-q theory, and switching signals are generated through multicarrier pulse width modulation (PWM) techniques. Study conducted in MATLAB for a single-phase balanced system demonstrate the effectiveness of the proposed topology. Results reveal a reduction in total harmonic distortion (THD) of the source current from 34.15% to 2.31%, meeting the IEEE-519 standard. The findings validate the proposed APF's capability to enhance power quality by mitigating harmonics. By integrating advanced MLI technology with artificial intelligence-based control, this work offers a cost-effective, efficient solution to improve the performance of polluted distribution networks.